The place of Kharkiv region in the restaurant business development of Ukraine - Кобилін, П.О. (My University, 2014)
The article analyses the dynamics of a number of restaurant business enterprises and retail trade turnover of restaurant enterprises in Ukraine and Kharkiv region, rating of the indexes which define restaurant enterprises activity per regions of Ukraine has been conducted by the method of linear scaling and the place of Kharkiv region has been defined
Материалы XVIII конференции молодых географов Сибири и Дальнего Востока с элементами научной школы (с международным участием) «Развитие географических знаний: научный поиск и новые методы исследования» (27-31 мая 2014 г.)
Keywords: bar; café; catering; restaurant; restaurant business